BETRAYAL OF LOVE ON PROTAGONIST IN ALEX MICHAELIDAS’ NOVEL THE SILENT PATIENT - Fitria Salsabila (Universitas Islam Sumatera Utara, 2023)
This research is entitled betrayal of love on protagonist in Alex Michaelidas’ novel The Silent Patient. This study focuses on the effect of the betrayal of love on protagonist. The data used in this study is obtained from the quotation in the novel. Collecting data is based on the theory, understandings, and explanations of betrayal of love. These are put forward by experts such as Fitness and the American Psychiatric Association. This study also uses the love theory of Stenberg. These theories are useful for providing understanding and explanations of betrayal and love related to research problems. In analyzing this research, qualitative research method was used. The result shows that there are four effects of betrayal of love on the protagonist in the novel The Silent Patient. They are revenge, loss of trust, loss of integrity, and betrayal trauma. Each of the effects contains three data and they are analyzed based on the theory.